Developing serious games. - Bergeron, Bryan, ....- (Hingham : Charles River, 2006)
With the impressive growth the games industry has enjoyed for the past decade, game developers, educators, and marketing firms are excitedly envisioning serious games applications for computer game technologies. These applications- serious games- represent opportunities for game developers to apply their talents to areas outside of the entertainment industry. Developing Serious Games is a practical handbook that details what's involved in developing these serious games. It explores the emergence of serious games as a viable niche in the multi-billion dollar gaming industry, and it covers the various types of serious games, including military, academic, medical, and training & development. From there it continues with a discussion of the enabling technology trends, emerging standards, and the tools that promise to reinforce the current trajectory of development and user demand for serious games. The second half of the book emphasizes the economic realities of the serious games industry, including and evaluation of the market, the economic potential of the space, and the customer base. The book culminates with a serious game design document that illustrates the important differences between entertainment games and serious games. It also provides a look to the future of serious gaming from a developer's perspective. The book is written for students, established game developers, and professionals in related fields, such as modeling and simulation or instructional design, who are skilled in training with traditional approaches and tools. It is also applicable to programmers, graphic artists, and management contemplating or involved in the development of serious games.